Genome-wide and rna-seq highlight genetic characteristics of rumpless signals in piao chicken - Wang Mei QI; Xing Fu ZHANG; Li Wen SONG; Zai Xia LIU; Yuan CHAI; Yan Yong SUN (Kafkas Universitesi Veteriner Fakültesi Dergisi)
Piao chicken is a unique rumpless chicken breed in China. Understanding the genetic relationship between rumpless chicken and other specific selection target breeds in the process of differentiation of the rumpless signal genes is helpful to reveal the genetic basis of rumplessnesss. In this study, transparent staining was performed on the bones of 16 tailed chickens and 16 Piao chickens to observe the dynamic bone formation process of embryos at different developmental stages. Microarray data of 988 chickens, resequencing results of 30 Piao chickens and 30 tailed chickens and 10 transcriptome samples were used for analysis. The results showed that tailbone development had tail buds before 4 to 6 days of incubation, and the difference was not significant between tailed chicken and Piao chicken, and the tail buds gradually degenerated in the later stage of Piao chicken. Most genes showed obvious inhibited expression in 8 d of embyro. We also found that exon skip was the most common type, and the PSI values of the ADGRL3 and PROM1 genes were differentially expressed between tailed chicken and Piao chicken of embryonic development constantly, which may be a special role that has not been recognized before. The network attributes of Piao chicken is tighter and the linkage between genes is stronger, especially the wnt signaling pathway and notch signaling pathway were mentioned.